Materfamilias - Cambridge, Ada, 1844-1926 (Salt Lake City, UT : Project Gutenberg, 2012)
"Materfamilias" by Ada Cambridge is a novel written in the late 19th century. The story centers on Mary, who navigates difficult personal choices after her father's remarriage to her governess, highlighting themes of love, duty, and resilience. As she embarks on a journey to re-establish a connection with her estranged husband, Edward, the narrative explores her relationships, self-discovery, and the societal pressures of the time. The opening of "Materfamilias" introduces us to Mary as she grapples with familial upheaval following her father's second marriage, and her decision to leave home rather than accept a new mother figure. Striking out on her own, Mary marries Edward in secrecy, but finds herself struggling with the harsh realities of life, particularly when she learns of her husband's illness in Australia. Determined to be by his side, she embarks on a challenging voyage aboard a small ship captained by Thomas Braye. Her feelings of vulnerability and the budding sense of companionship with Captain Braye set the stage for Mary$1 (Bs growth and transformation throughout the narrative. The opening thus lays the groundwork for an exploration of marriage, independence, and the complexities of motherhood amid societal expectations. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Materfamilias
Release date is 2012-09-04
Produced by Clare Graham, Laura McDonald at http://www.girlebooks.com & Marc D'Hooghe (Images graciously made available by the Internet Archive.)
Keywords: Australia -- Fiction; Family life -- Fiction; Married women -- Fiction; Mothers -- Fiction